Storytelling of Political Leaders as an Instrument of Symbolic Politics - S. V. Gerasimov; P. A. Tereshchenko (Дискурс, 2020)
Introduction. The article attempts to analyze the attempts of political leaders of various types to build political communications in the new social reality - on the Internet. The material of the study was taken from the storytelling of the three leaders in social networks during the first attempts to create elements of symbolic politics. In the process of analyzing this narration, we asked ourselves: - How much is the traditional image of a particular political leader related to his reflection on social networks? The relevance of the author's approach lies in the analysis of storytelling as a tool for the formation of symbolic politics and social reality. Political leaders moved into a virtual environment following their target audiences.Methodology and sources. The methodological basis of the work is verification on practical material of socio-philosophical concepts and models of political analysts, cultural scientists, sociologists (P. Shtompki, V.A. Yadova, O.Yu. Malinova, G.L. Tulchinsky and others). The article uses narratives obtained from open access social networks. To clarify the formation of social reality, a comparative analysis of the narratives of public leaders regarding the creation of a space of symbolic politics was carried out.Results and discussion. As a result of the study, theoretical models that describe the behavioral patterns of political leaders in the information society were verified. In the modern information society, the main focus is transferred to social networks, where the target audience of political figures spend their time. Political leaders follow their target audience in different ways by showing their presence on social networks, both quantitative and qualitative. As a result of the study, the distinctive features of storytelling of public politicians, the similarities and differences in the technologies for creating a full-fledged image of a leader in the mass consciousness of the target audience, the similarities and differences between the image of a political leader taking shape in traditional media and on the Internet are clarified.Conclusion. In 2018, we observe the phenomenon of the entry into the space of social networks of politicians with the aim of event formation of elements of symbolic politics. In the study of storytelling as a process of forming public communications, the roles of sources and actors are defined. In today's digital society, social networks play a critical role in the processes of generating social reality. The mechanisms for the formation of narratives may require additional research, but now we can determine their impact on the political, socio-cultural and business environment.